Arsenic wastewater treatment agent, preparation method, application and arsenic wastewater treatment method

By using Bacillus subtilis W7 and iron-modified biochar in the prior art, the problems of low treatment efficiency and high cost of treatment solutions are solved, and efficient and stable removal of arsenic pollutants is achieved, which is suitable for industrial applications.

CN119858984AActive Publication Date: 2025-04-22QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)

Patent Information

Application Number
CN202510344325.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The prior art has problems such as insufficient single treatment efficiency, lack of coordination mechanism for joint treatment, weak universality of treatment solutions and high cost when treating arsenic-contaminated wastewater, and is prone to secondary pollution.

Method used

By using Bacillus subtilis W7 in conjunction with iron-modified biochar, an arsenic wastewater treatment agent was prepared, which utilized the adsorption capacity of iron-modified biochar and the biorepair ability of the strain to synergize the arsenic content in the water.

Benefits of technology

It has achieved efficient removal of arsenic pollutants, with stable performance and controllable cost, is suitable for industrial applications, and has green and environmentally friendly biological approaches.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119858984A_ABST
    Figure CN119858984A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wastewater treatment, and particularly relates to an arsenic wastewater treatment agent, a preparation method, application and an arsenic wastewater treatment method.The arsenic wastewater treatment agent comprises a carrier and a bacterial suspension adsorbed and fixed to the carrier; the carrier is iron modified biochar; the bacterial strain in the bacterial suspension is bacillus subtilis W7, and the bacterial strain in the bacterial suspension is bacillus subtilis W7. The bacterium-carbon composite material prepared through freeze drying can be compatible with multifunctional additives (such as iron oxide), can quickly activate the metabolic activity of strains through rehydration, and is suitable for groundwater remediation or industrial prefabricated remediation agent production with large temperature difference and high storage requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and specifically relates to an arsenic wastewater treatment agent, a preparation method, an application and an arsenic wastewater treatment method. Background Art

[0002] Arsenic is an element widely distributed in the natural environment. When the arsenic content in the water accumulates to a certain level, it will harm aquatic organisms in the water and endanger human health through the food chain and other pathways. For the treatment of arsenic-contaminated wastewater, treatment agents such as modified biochar, microbial agents, and the combination of the two are often used. The current treatment technology for arsenic-contaminated wastewater has significant limitations: 1) The efficiency of a single treatment is insufficient. For example, although the application of iron-based biochar alone can adsorb part of the arsenic, traditional modification methods such as low iron loading or non-optimized pyrolysis processes are prone to saturation or desorption risks of adsorption sites; and although the application of microbial agents alone can transform arsenic forms, they have poor tolerance to high concentrations of arsenic and cannot block the absorption of aquatic plants or animals; 2) The existing combined treatment technology lacks a synergistic mechanism, does not optimize the adaptability of bacteria-carbon, leads to clogging of biochar pores, thereby inhibiting bacterial activity, and the remediation efficiency is lower than that of a single component; 3) The treatment scheme has weak universality, high cost and is prone to secondary pollution.

[0003] In the prior art, physical adsorption, co-cultivation, chemical cross-linking and embedding methods are often used to load strains onto biochar. However, the load capacity of physical adsorption is low and easy to fall off, and the co-cultivation cycle is long and the efficiency is low. The chemical reagents in chemical cross-linking can easily damage the activity of the bacteria. The mass transfer in the embedding method is limited. At the same time, in long-term remediation scenarios, physically adsorbed bacteria are easily eroded and fall off by environmental erosion, chemical cross-linking may introduce secondary pollution, and co-cultivation is difficult to control the load density. Therefore, there is an urgent need for some bacteria-charcoal composite materials and preparation methods that can maintain high survival rates of strains, ensure load uniformity and prolong material stability, which are of great significance for efficient arsenic pollution control. Summary of the invention

[0004] The purpose of the present invention is to provide an arsenic wastewater treatment agent, a preparation method, an application and an arsenic wastewater treatment method, so as to overcome the shortcomings of the prior art and synergistically reduce the content of arsenic pollution in water bodies by strain W7 and iron-modified biochar.

[0005] In order to achieve the above object, the technical solution of the present invention is: In a first aspect, the present invention provides an arsenic wastewater treatment agent, comprising a carrier and a bacterial suspension adsorbed and fixed on the carrier; The carrier is iron-modified biochar; The strain in the bacterial suspension is Bacillus subtilis (Bacillus subtilis) W7.

[0006] In some other embodiments, the mass ratio of carbon to iron in the iron-modified biochar is 1:(0.025-1.5); The iron-modified biochar has a pH of 8-9, a conductivity of 1800-1900 μs / cm, an ash content of 25-30 wt%, and a specific surface area of ​​10-12 m 2 / g, with a total pore volume of 0.05-0.07cm 3 / g, the average pore size is 20-22nm, the adsorption pore diameter is 22-24nm, and the desorption pore diameter is 17-19 nm.

[0007] In some other embodiments, the OD600 of the bacterial suspension is 0.9-1.1; and the ratio of the carrier to the bacterial suspension is 1 g: (5-30) mL.

[0008] In a second aspect, the present invention provides a method for preparing the arsenic wastewater treatment agent described in the first aspect, comprising the following steps: under sterile conditions, mixing iron-modified biochar with a bacterial suspension, and freeze-drying the mixture to obtain the arsenic wastewater treatment agent.

[0009] In some other embodiments, the method for preparing the iron-modified biochar comprises the following steps: (1) The straw powder is heated to 350-450°C under anaerobic conditions, kept warm for 1-3 hours, cooled to room temperature, and sieved to obtain biochar; (2) Add water to the mixture of biochar and iron source for reaction, dry it, heat it to 350-450°C under anaerobic conditions, keep it warm for 0.5-1h, cool it to room temperature, and seal it to obtain iron-modified biochar.

[0010] In some other embodiments, in step (1), the particle size of the straw powder is less than 1 mm, and the particle size of the biochar is 0.053 mm -1 mm; In step (2), the iron source is one of ferric nitrate nonahydrate, ferrous chloride, ferric chloride and ferric sulfate; The mixing mass ratio of the biochar to the iron in the iron source is 1: (0.025-1.5); The solid-liquid ratio of the mixture to water is 1 g: (25-35) mL; The reaction is carried out at a constant temperature of 25-30°C and a shaking reaction at 150-200 r / min for 10-15 hours; The drying temperature is 50-60°C.

[0011] In some other embodiments, the method for preparing the bacterial suspension comprises the following steps: Bacillus subtilis ( Bacillus subtilis) W7 is inoculated into a sterilized LB liquid medium and cultured in the dark to obtain a seed solution, the seed solution is mixed with the sterilized medium, and the culture is continued in the dark to obtain a bacterial suspension; The sterilization temperature is 121°C for 0.5-1h; the light-proof culture is a constant temperature culture of 25-30°C with shaking at 150-200r / min for 20-25h; The continued dark-proof culture is carried out at a constant temperature of 25-30° C. and a shaking culture at 150-200 r / min for 1-2 days; The volume ratio of the seed solution to the sterilized culture medium is 1:(20-30); The OD600 in the seed solution is 0.6-1; The OD600 of the bacterial suspension is 0.9-1.1.

[0012] In some other embodiments, the ratio of the iron-modified biochar to the bacterial suspension is 1 g: (5-30) mL; The mixing is carried out at a constant temperature of 30-40°C and at a shaking speed of 150-200 r / min for 1-12 hours; The freeze drying is firstly freezing at -75~ -85°C for 0.5-2h, and then freezing at -45~ -55°C under vacuum for 20-30h.

[0013] In a third aspect, the present invention provides use of the arsenic wastewater treatment agent described in the first aspect in arsenic-contaminated water bodies.

[0014] In a fourth aspect, the present invention provides a method for treating arsenic wastewater, wherein the arsenic wastewater treating agent described in the first aspect is applied to an arsenic-contaminated water body; The arsenic content in the water body is 0-100 mg / L, and the temperature of the water body is 10-30°C; The application amount of the arsenic wastewater treatment agent is 1-5 g / L, and the application time is 20-30 hours.

[0015] Beneficial effects of the present invention: (1) The iron-modified biochar prepared in the present invention serves as the main active component for arsenic adsorption, and its adsorption capacity is significantly improved through coordination and chemical complexation. At the same time, the iron-modified biochar has a suitable pH environment, high conductivity, inorganic phase distribution, and a pore structure with an enlarged specific surface area and pore volume, which can efficiently remove arsenic pollutants and provide a solution with stable performance and controllable cost for industrial applications.

[0016] (2) The strain W7 in the present invention completes the entire cycle from adaptation to efficient reproduction within 12 hours, showing the potential for short-term high-density culture and high-concentration arsenic tolerance, and is suitable for industrial fermentation, bioremediation and other fields.

[0017] (3) The synergistic effect between the bacteria and iron-modified biochar in the present invention is enhanced, and its mechanism integrates physical and chemical adsorption (FB-3 quickly fixes arsenate), bioaugmentation (W7 secretes extracellular polymers to drive arsenic reduction and mineralization) and structural protection (biochar maintains the long-term activity of the bacteria); it is both efficient and sustainable, providing an innovative solution for the control of arsenic pollution in farmland and has the potential for industrial promotion.

[0018] (4) The freeze-dried bacteria-carbon composite material of the present invention is not only compatible with multifunctional additives (such as iron oxides), but also can quickly activate the metabolic activity of the strain through rehydration. It is suitable for groundwater remediation with large temperature differences and high storage requirements or for the production of industrial prefabricated remediation agents. Its technical advantages of high activity retention and stability make it the preferred loading method for efficient arsenic pollution control.

[0019] (5) The treatment agent of the present invention has the advantages of simple process, convenient operation, low treatment cost, high treatment efficiency, good removal effect, etc. It has high use value and good application prospects, and provides a green and environmentally friendly biological approach for the treatment of arsenic in water. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0021] Figure 1 It is the adsorption rate of As by the original biochar and the iron-modified biochar prepared with different iron modification ratios in the embodiments of the present invention, wherein BC is the original biochar, FB-1 is the iron-modified biochar with a carbon-iron mass ratio of 1:0.025, FB-2 is the iron-modified biochar with a carbon-iron mass ratio of 1:0.05, FB-3 is the iron-modified biochar with a carbon-iron mass ratio of 1:0.1, FB-4 is the iron-modified biochar with a carbon-iron mass ratio of 1:1.25, and FB-5 is the iron-modified biochar with a carbon-iron mass ratio of 1:1.5; Figure 2 : are scanning electron microscope images of the original biochar and the iron-modified biochar FB-3 in the embodiment of the present invention, wherein A, B, and C are scanning electron microscope images of the original biochar at 10 μm, 5 μm, and 2 μm scales; D, E, and F are scanning electron microscope images of the iron-modified biochar FB-3 at 10 μm, 5 μm, and 2 μm scales; Figure 3 This is a diagram showing the EDS quantitative results of the original biochar and the iron-modified biochar FB-3 in the embodiment of the present invention; Figure 4 The growth curve, adsorption effect and tolerance curve of strain W7 were tested at different times in the embodiment of the present invention, where A is the growth curve, B is the adsorption effect, and C is the tolerance curve; Figure 5 The effect of the inoculation ratio and fixation time of W7FB on the arsenic adsorption performance in the embodiment of the present invention, wherein A is the inoculation ratio and B is the fixation time; Figure 6 The scanning electron microscope test image of W7FB in the embodiment of the present invention, wherein A, B, and C are scanning electron microscope images of W7FB at 10 μm, 5 μm, and 2 μm scales; Figure 7 The adsorption effect of W7FB on arsenic at different times in the embodiment of the present invention; Figure 8 The pseudo-first-order and pseudo-second-order kinetic models are fitted to the arsenic adsorption process of W7FB in the embodiment of the present invention, where A is the pseudo-first-order kinetic model and B is the pseudo-second-order kinetic model; Fig. 9 is the fitting result of the isothermal adsorption model in the embodiment of the present invention; Fig.10 This is the repair effect of different dosages on water bodies at different temperatures in the embodiments of the present invention. DETAILED DESCRIPTION

[0022] Those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. Specific conditions are not specified in the examples, and the conventional conditions or conditions recommended by the manufacturer are used. The components used without indicating the manufacturer are all conventional products available on the market.

[0023] Example 1 (1) Preparation of iron-modified biochar Preparation of biochar (marked as BC): corn straw powder that has passed through a 1mm diameter sieve is placed in a 200ml porcelain crucible with a lid, sealed with tin foil, and placed in a muffle furnace. It is heated from room temperature to 400°C at a heating rate of 5-10°C / min under anaerobic conditions and maintained for two hours. After cooling to room temperature, it is passed through 1mm and 0.053mm diameter sieves, and the middle part is the original biochar (marked as BC).

[0024] Preparation of Fe-modified biochar (labeled as FB): The original biochar was mixed with ferric nitrate nonahydrate in a carbon:iron mass ratio of 1:0.025, 1:0.05, 1:0.1, 1:1.25, and 1:1.5, placed in a conical flask containing deionized water (solid-liquid ratio 1:30), and reacted in a constant temperature oscillator at 30 °C and 180 r / min for 12 h. After the shaking, the conical flask was repeatedly washed with deionized water, and the mixture was placed in a glass tray, which was placed in an oven and dried at 50°C. After drying, the mixture was sealed with tin foil and placed in a muffle furnace under anaerobic conditions, heated from room temperature to 400°C at a heating rate of 5-10°C / min, and maintained for thirty minutes. After being taken out, the mixture was sealed and stored, and labeled as iron-modified biochar FB-1 (carbon-iron mass ratio 1:0.025), FB-2 (carbon-iron mass ratio 1:0.05), FB-3 (carbon-iron mass ratio 1:0.1), FB-4 (carbon-iron mass ratio 1:1.25), and FB-5 (carbon-iron mass ratio 1:1.5).

[0025] The prepared original biochar (BC) and iron-modified biochar (FB) with different proportions were tested, and the results are as follows: Figure 1 It is the removal rate of As by original biochar and iron-modified biochar prepared with different iron modification ratios, where BC is original biochar, FB-1 is iron-modified biochar with a carbon-iron mass ratio of 1:0.025, FB-2 is iron-modified biochar with a carbon-iron mass ratio of 1:0.05, FB-3 is iron-modified biochar with a carbon-iron mass ratio of 1:0.1, FB-4 is iron-modified biochar with a carbon-iron mass ratio of 1:1.25, and FB-5 is iron-modified biochar with a carbon-iron mass ratio of 1:1.5; the letters marked on the bar graph (such as a, b, c) represent the results of the multiple comparison test, which are used to intuitively display the significant differences between different groups. If two groups are marked with the same letter, it means that there is no statistically significant difference in their mean values ​​(p ≥ 0.05). If two groups are marked with different letters (such as a and b), it means that there is a significant difference in their mean values ​​(p<0.05). If two letters are marked at the same time, such as bc, it indicates that the data group belongs to two groups with no statistically significant difference.

[0026] from Figure 1It can be seen that the original biochar BC has a low arsenic removal rate of only 35.3% due to the lack of iron active sites; after iron modification, the adsorption performance shows a trend of first increasing and then decreasing with the increase of iron ratio: among the low-ratio iron loadings (FB-1 to FB-3), FB-3 (carbon-iron ratio 1:0.1) reached a peak value, and the arsenic removal rate reached 57.2%, indicating that an appropriate amount of iron loading can effectively increase the active sites and optimize the pore structure of the material; however, excessive iron (FB-4, FB-5) caused a significant decrease in arsenic removal rate due to iron agglomeration and pore blockage. Therefore, the present invention adopts FB-3 (carbon-iron ratio 1:0.1) as the best iron-modified biochar, and FB-3 is used as the iron-modified biochar for further research in subsequent studies.

[0027] Table 1 shows the physical and chemical properties of original biochar BC and iron-modified biochar FB-3; Table 2 shows the pore structure parameters of original biochar BC and iron-modified biochar FB-3.

[0028] Table 1 shows the physical and chemical properties of the original biochar BC and iron-modified biochar FB-3

[0029] As can be seen from Table 1, the pH of the original biochar BC was 9.45±0.15, and the pH of the iron-modified biochar FB-3 dropped to 8.76±0.11, which was closer to neutral conditions and was conducive to the electrostatic adsorption of arsenate ions; the conductivity increased from 1257±2.14 μs / cm to 1823±1.59 μs / cm, indicating that the surface active sites and ion exchange capacity of FB-3 were enhanced; the ash content increased from 20.7% to 28.4%, confirming the successful loading of iron oxides (the iron in the iron-modified biochar mainly exists in the form of iron oxides, such as Fe 3 O 4 、FeO(OH)、γ-Fe 2 O 3 , α-Fe 2 O 3 wait).

[0030] Compared with biochar modified by zero-valent iron, the iron-modified biochar FB-3 of the present invention has the following advantages: enhanced adsorption performance, iron oxide can provide more adsorption sites; improved stability, iron oxide has good stability in the environment, and can maintain adsorption performance for a long time; the preparation method of iron-modified biochar is relatively mature, low cost, and easy to mass produce. As the main active component for arsenic adsorption, it significantly improves the adsorption capacity through coordination and chemical complexation. The iron-modified biochar of the present invention has a suitable pH environment, high conductivity and optimized inorganic phase distribution, can efficiently remove arsenic pollutants in water, and provides a stable performance and cost-controlled solution for industrial applications.

[0031] Table 2 Pore structure parameters of original biochar BC and iron-modified biochar FB-3

[0032] As can be seen from Table 2, the BET specific surface area of ​​the original biochar BC is only 7.17 m² / g, the total pore volume is 0.011 cm³ / g, and the average pore diameter is 6.177 nm, indicating that it is mainly micropores and the pore development is limited; while the BET specific surface area of ​​the modified biochar FB-3 is increased to 11.965 m² / g (an increase of about 67%), the total pore volume is increased to 0.062 cm³ / g (an increase of nearly 5 times), and the average pore diameter is expanded to 21.041 nm, proving that the iron loading effectively widens the pores and forms a mesoporous-macroporous hierarchical structure. At the same time, the BJH adsorption pore diameter is reduced from 30.914 nm to 23.35 nm, and the desorption pore diameter is increased from 15.92 nm to 18.91 nm, indicating that the iron oxide modification optimizes the pore connectivity and reduces the discreteness of the pore size distribution. This structural property synergistically improves the material's adsorption performance for arsenic: the enlarged specific surface area and pore volume increase the exposed area of ​​active sites, the graded pores promote the diffusion and retention of arsenate ions, and the homogenization of pore size enhances the adsorption stability. The above pore regulation mechanism provides key structural support for the efficient arsenic adsorption of iron-modified biochar.

[0033] Figure 2 The following are scanning electron micrographs of the original biochar BC and the iron-modified biochar FB-3, where A, B, and C are scanning electron micrographs of the original biochar at 10 μm, 5 μm, and 2 μm scales; and D, E, and F are scanning electron micrographs of the iron-modified biochar FB-3 at 10 μm, 5 μm, and 2 μm scales. Figure 2 It can be seen that the surface of iron-modified biochar FB-3 is rougher than that of original biochar BC and has more adsorption sites.

[0034] The EDS quantitative results of original biochar BC and iron-modified biochar FB-3 are shown in Table 3.

[0035] Table 3 shows the EDS quantitative results of the original biochar BC and iron-modified biochar FB-3

[0036] As can be seen from Table 3, through the EDS elemental analysis of biochar (BC) and its iron-modified material (FB-3), it can be clearly seen that the iron modification process has a significant effect on the surface composition of the material: the iron loading effect is outstanding: the mass percentage of Fe is greatly increased from 0.68% to 39.5% (the atomic percentage increases from 0.18% to 14.95%), indicating that iron oxides (such as FeOOH, Fe 3 O 4) were successfully loaded on the surface and pores of biochar, providing abundant active sites for arsenic adsorption. Carbon skeleton oxidation and oxygen enrichment: The mass percentage of C dropped sharply from 57.5% to 22.7% (the atomic percentage dropped from 70.23% to 40.12%), indicating that the carbon skeleton was partially oxidized or formed a composite structure with iron during the modification process; at the same time, the mass percentage of O increased from 19.72% to 28.7% (the atomic percentage increased from 18.06% to 38.04%), indicating that iron oxides and surface oxygen-containing functional groups (-OH, -COOH) increased significantly, further enhancing the coordination adsorption capacity of arsenic. Silicon content decreased: The mass percentage of Si dropped from 22.1% to 9.1% (the atomic percentage dropped from 11.53% to 6.89%), which may be due to the partial dissolution of silicates due to iron coverage or high-temperature modification, but it has little effect on the adsorption performance. Iron-modified biochar FB-3 significantly optimized its functional properties as an arsenic adsorbent through efficient loading of iron oxides and surface oxidation modification. In particular, the synergistic effect of iron and oxygen laid a chemical foundation for the subsequent combined remediation of strain W7, making it suitable for the efficient treatment of highly arsenic-contaminated water bodies.

[0037] Figure 3 The EDS quantitative results of the original biochar BC and the iron-modified biochar FB-3 are shown in the figure. The spectrum of the original biochar (BC) is dominated by carbon (C-Kα peak, 0.28 keV), followed by oxygen (O-Kα peak, 0.53 keV), and the iron signal (Fe-Kα peak, 6.4 keV) is weak. The intensity of the Fe-Kα peak in the spectrum of the iron-modified biochar (FB-3) is significantly enhanced, confirming that the iron oxides are uniformly loaded on the surface of the carbon matrix in the form of nanoparticles, which is consistent with the roughened morphology observed by SEM. The significant weakening of the C-Kα peak indicates that iron covers part of the carbon structure, while the increase in the O-Kα peak intensity is due to the contribution of hydroxyl groups (-OH) and calcium-based minerals on the surface of the iron oxides. This change in chemical composition and the spectral characteristics together indicate that iron oxides synergistically enhance the chemical adsorption and physical retention of arsenic by providing abundant hydroxyl sites and optimizing the pore structure.

[0038] (2) Shake flask experiment: Adsorption effect and growth of W7 bacteria on arsenic The shake flask experiment bacteria used in the present invention is Bacillus W7 (taxonomic name Bacillus subtilis) disclosed in application number 202010531482.9 Bacillus subtilis ).

[0039] Preparation of bacterial suspension: LB liquid culture medium was measured and placed in a conical flask, and sterilized at 121°C in a high-pressure steam sterilizer for 20 min. Under the clean bench, a sterile inoculation loop was used to pick the preserved strain and inoculate it into the sterilized medium. The suspension was cultured in a constant temperature oscillator at 30°C and 150 r / min in the dark for 24 h. At this time, the bacterial growth entered the logarithmic phase (OD600 between 0.6 and 1), and this was used as the seed liquid.

[0040] Use LB liquid medium as the base liquid, inoculate the target seed liquid at a volume ratio of 1:25 (seed liquid: base liquid), and repeat the above culture process until the OD600 of the bacterial suspension reaches about 1 (usually 1-2 days can meet the requirements). Use UV-visible spectrophotometry (wavelength 600 nm) to measure the growth curve of the strain and determine the optimal ratio between the strain and charcoal in the later stage.

[0041] Arsenic tolerance experiment: 37℃, 180 rpm constant temperature shaking culture for 18 h until the logarithmic growth phase. Take the bacterial solution and transfer it to the arsenic-containing As medium at a 1% (v / v) inoculation volume. 5+ Sterile arsenic solution was added to LB medium to a final concentration of 0, 20, 40, 60, 80, and 100 mg / L. Three parallels were set up for each group, and the culture was continuously shaken at 37 °C for 12 h. Samples were taken every 2 h, and the absorbance of the bacterial solution was measured using an ELISA reader (wavelength 625 nm), and the changes in OD values ​​at each time point were recorded. The growth curve of strain W7 in medium with different arsenic concentrations was observed to determine its sensitivity to As. 5+ degree of tolerance.

[0042] Arsenic adsorption test: The arsenic adsorption test was a shake flask experiment. The cultured strain W7 seed liquid was placed in a culture medium with an arsenic content of 50 mg / L and cultured for 24 hours. The arsenic concentration after adsorption was detected using icp-MS, and the removal rate was calculated.

[0043] The growth curve, adsorption effect and tolerance curve of strain W7 were tested at different times. The results are as follows: Figure 4 As shown, A is the growth curve, B is the adsorption effect, and C is the tolerance curve. The present invention relates to the growth characteristics of strain W7 and its application in microbial engineering. The experiment revealed its significant growth kinetic characteristics by monitoring the changes in OD600 value (optical density value) of strain W7 from 0 to 12 hours. Figure 4As shown in A: In the initial stage (0-2 hours), the strain is in a delayed period, and the OD value rises slowly (from 0.2 to 0.4), indicating that the bacteria gradually adapt to the culture environment and start metabolic activities; then enter the logarithmic growth period (2-8 hours), the OD value increases exponentially (0.4 to 1.0), indicating that the bacteria proliferate rapidly and the metabolic activity reaches a peak; in the stable period (8-12 hours), the OD value growth rate slows down (1.0 to 1.2), indicating that nutrient limitation or accumulation of metabolites leads to a decrease in growth rate. Strain W7 completes the entire cycle from adaptation to efficient reproduction within 12 hours, showing the potential for short-term high-density culture, and is suitable for industrial fermentation, bioremediation and other fields.

[0044] The present invention relates to the application of strain W7 in the field of arsenic adsorption and its time-dependent adsorption characteristics. The experiment monitored the arsenic adsorption dynamics of strain W7 from 0 to 12 hours and found that its adsorption efficiency was highly correlated with the growth stage. Figure 4 As shown in B: In the initial stage (0-2 hours), the strain is in the growth delay period, and the arsenic removal rate slowly increases to 23%, mainly relying on the physical adsorption of surface functional groups (such as hydroxyl and carboxyl groups); in the logarithmic growth period (2-8 hours), the metabolic activity of the bacteria is enhanced, and the adsorption rate quickly rises to 33%. The secretion of extracellular polymers (EPS) and the chemical complexation mediated by iron carriers significantly enhance the fixation of arsenic; in the stable period (8-12 hours), the adsorption rate reaches a peak of 33% and tends to equilibrium, indicating that the bacteria further optimize the adsorption capacity through biomineralization or intracellular enrichment mechanism.

[0045] The growth curves (OD600 values) of strain W7 at different arsenic concentrations showed that it had significant arsenic tolerance: it could grow in the arsenic concentration range of 0-100 mg / L, but its proliferation ability decreased with increasing arsenic concentration. Figure 4 As shown in C: Arsenic-free conditions (0 mg / L): OD600 continued to increase from 0.32 to 1.12 (12 hours), showing a typical logarithmic growth period, and the strain activity was not inhibited; low arsenic concentration (20-40 mg / L): OD600 reached 0.79 and 0.75 at 12 hours, respectively, down 29.5% and 33.0% from the blank group, indicating mild inhibition but still maintaining high metabolic activity; high arsenic concentration (60-100 mg / L): OD600 peaks dropped to 0.70 (60 mg / L) and 0.62 (100 mg / L), inhibition rates reached 37.5% and 44.6%, respectively, and the logarithmic growth period was shortened (the growth rate slowed down after 8 hours), indicating that arsenic stress caused the bacteria to enter the stable period ahead of time; half inhibition concentration (IC~50~): based on the 12-hour data, IC~50~ is estimated to be about 80-100 mg / L (the concentration range corresponding to a 50% decrease in OD600).

[0046] Conclusion: Strain W7 has strong tolerance to high concentration of arsenic (≤100 mg / L) and is suitable for bioremediation of medium- and high-arsenic contaminated environments (such as industrial wastewater and high-arsenic groundwater). However, its optimal activity window is arsenic concentration ≤60 mg / L (inhibition rate <40%), within which efficient metabolism and arsenic adsorption performance can be guaranteed.

[0047] (3) Optimization of bacteria-loaded biochar composites Preparation of composite materials: Iron-modified biochar FB-3 was used as a carrier, and the strain was fixed by immersion adsorption method to prepare a composite material. The specific preparation method is as follows: iron-modified biochar FB-3 was weighed in a conical flask, sterilized at 121°C with high-pressure steam for 20 min, and cooled to room temperature. Under sterile conditions, the above bacterial suspension was inoculated at a ratio of 1:20 of iron-modified biochar FB-3: bacterial suspension (W:V), and adsorption and fixation were completed by shaking at 30°C and 150 r / min for 4h. After centrifugation, the precipitate was washed with 1% sterile saline, and the washing was repeated three times. The precipitate obtained was the loaded material, and the material of bacteria W7 loaded with iron-modified biochar FB-3 was recorded as W7FB.

[0048] Optimization of strain inoculation amount: Weigh the modified biochar FB-3 in a conical flask, sterilize at 121°C for 20 min, inoculate the bacterial suspension at a ratio of 1:5, 1:10, 1:20, and 1:30 of modified biochar FB-3: bacterial suspension (W:V), shake culture at 30°C and 150 r / min for 24 h, and obtain the loaded materials under different strain inoculation amounts after centrifugation and washing. Weigh 0.5 g of each of the above materials and place them in a 100 mL conical flask, and add 50 mL of 50 mg·L -1 The sterilized As solution was cultured on a constant temperature oscillator at 30°C and 150 r / min for 12 h, centrifuged at 5000 r / min for 5 min, and the supernatant was filtered through a 0.45 μm filter membrane to determine its As concentration and calculate the adsorption amount to determine the optimal strain inoculation amount for the loading material.

[0049] Optimization of immobilization time: Weigh the iron-modified biochar FB-3 in a conical flask, sterilize at 121°C for 20 min, inoculate the bacterial suspension at a ratio of 1:10 of iron-modified biochar FB-3: bacterial suspension (W:V), shake culture at 30°C and 150 r / min, and end the culture at 0, 1, 2, 3, 4, 8, and 12 h, respectively. After centrifugation and washing, the loaded materials at different immobilization times were obtained. Repeat the above adsorption experiment, measure the As concentration, and determine the optimal immobilization time of the composite material.

[0050] The prepared bacteria W7 loaded iron-modified biochar FB-3 composite material was freeze-dried and set aside for later use. The specific process is as follows: the cultured strain W7 resuspension is mixed with the iron-modified biochar FB-3 in proportion, and shaken and cultured in a constant temperature shaking shaker at 37°C and 150 r / min for the optimal fixation time. After fixation, it is placed in a -80°C refrigerator for 1 hour to freeze into solid ice, and then placed in a vacuum freeze dryer and freeze-dried at -50°C in a vacuum environment for 24 hours. The obtained powder is the bacteria W7 loaded iron-modified biochar FB-3 material.

[0051] During the research, the inventors found that among the various methods of strain-loaded biochar, freeze-drying has become the preferred option due to its unique comprehensive advantages. Compared with physical adsorption (low load, easy to fall off), co-cultivation (long cycle), chemical cross-linking (damage to bacterial activity) and embedding method (limited mass transfer), freeze-drying fixes the bacteria through low-temperature dehydration, and performs outstandingly in maintaining a high survival rate of the strain (80%-90%), ensuring uniformity of load (uniform distribution of bacteria in the pores) and prolonging material stability (6-12 months of storage at room temperature). Its limitations in long-term remediation scenarios are significant: for example, physically adsorbed bacteria are easily eroded and fall off by environmental scouring, chemical cross-linking may introduce secondary pollution, and co-cultivation is difficult to control the load density. Freeze-dried bacteria-charcoal composite materials are not only compatible with multifunctional additives (such as iron oxides), but also can quickly activate the metabolic activity of strains through rehydration, which is suitable for groundwater remediation with large temperature differences and high storage requirements or industrial prefabricated remediation agent production. Therefore, its technical advantages of high activity retention and stability make it the preferred loading method for efficient arsenic pollution control.

[0052] The effects of the inoculation ratio and fixation time of W7FB on the arsenic adsorption performance were tested. Figure 5 As shown, A is the inoculation ratio and B is the fixed time.

[0053] The present invention optimizes the adsorption performance of strain W7 and biochar composite material (W7FB) and controls the inoculation ratio. The present invention compares the arsenic adsorption performance of different biochar and bacterial suspension inoculation ratios (1:5 to 1:30, W:V) as shown in the following results. Figure 5 As shown in A in the figure, the results showed that the adsorption efficiency showed a significant threshold effect. Specifically, at a low inoculation ratio (1:5), insufficient bacterial suspension resulted in incomplete coverage of active sites on the biochar surface, and the arsenic removal rate was only 63%; as the ratio increased to 1:10, the synergistic effect of bacteria and biochar was enhanced, and the removal rate increased to a peak of 75%. At this time, iron oxides and extracellular polymers (EPS) secreted by bacteria formed a composite adsorption interface, enhancing the chemical complexation and biological reduction of arsenic; however, at high inoculation ratios (1:20, 1:30), excessive bacterial suspension did not increase the arsenic removal rate.

[0054] The present invention relates to a method for optimizing the dynamic adsorption process of a composite material of strain W7 and biochar, and the effect of adjusting the fixation time of bacterial suspension and biochar (1-18 hours, inoculation ratio 1:10 W:V) on arsenic removal rate is as follows Figure 5 As shown in Figure B, the study found that the arsenic removal rate showed a two-stage characteristic of "rapid response-stable maintenance": in the initial fixation stage (1-4 hours), the bacteria quickly attached to the biochar surface and activated metabolic activity, and the arsenic removal rate increased from 60.8% to 66.1% (peak value), indicating that iron oxides and extracellular polymers (EPS) secreted by the bacteria synergistically formed an efficient adsorption interface; during the stable maintenance period (4-12 hours), the removal rate was maintained at 64.6%-65.7%, with a fluctuation range of less than 2%, proving that the composite material still maintains stable adsorption performance during long-term action, and its mechanism may be attributed to the protective effect of the biochar hierarchical pore structure (BET specific surface area 11.96 m² / g, average pore size 21.04nm) on the active sites of the bacteria; experiments showed that 4 hours was the optimal adsorption equilibrium time, at which time the arsenic removal rate reached 66.1%, and the material had both high efficiency and stability (efficiency >64% within 12 hours).

[0055] The results of scanning electron microscopy test on the prepared W7FB are as follows Figure 6 As shown, A, B, and C are scanning electron microscope images of W7FB at 10μm, 5μm, and 2μm scales. Figure 6 It can be seen that strain W7 was successfully loaded on the iron-modified biochar FB-3.

[0056] (4) Adsorption kinetics and adsorption isotherm of W7FB biochar material loaded with iron Weigh 0.1 g of strain W7 loaded with iron-modified biochar material W7FB into a 100 mL conical flask and add 50 mL of 100 mg / L As 5+ The solution was shaken and cultured in a constant temperature shaking incubator at 25°C and 150 r / min. Sampling was performed at 0, 10, 30, 60, 120, 180, 240, 300, 360, 480, 600, and 720 min, respectively. After standing, the upper layer of the solution was filtered through a 0.45 μm filter membrane and the adsorption amount was determined and calculated using ICP-MS. Three parallel samples were set for each sample.

[0057] The experimental results were fitted using pseudo-first-order kinetic model and pseudo-second-order kinetic model, where the pseudo-first-order kinetic model is shown in formula (1):

[0058] Where: q e is the adsorption amount when reaching equilibrium (mg / g), q t is the adsorption amount at time t (mg / g), k1 is the adsorption rate constant of the pseudo-first-order kinetic model.

[0059] The pseudo-second-order kinetic model is shown in formula (2):

[0060] Where: q e is the adsorption amount when reaching equilibrium (mg / g), q t is the adsorption amount at time t (mg / g), k 2 is the adsorption rate constant of the pseudo-second-order kinetic model.

[0061] Isothermal adsorption model: Weigh 0.1 g of W7 loaded iron-modified biochar material W7FB in a 100 mL conical flask and add 50 mL of As 5+ Solution, set As 5+ The initial concentrations were 0, 5, 10, 20, 40, 60, 80, and 100 mg / L, respectively. The cultures were shaken in a constant temperature shaker at 25°C and 150 r / min. After reaching adsorption equilibrium (720 min in this study), the upper layer solution was allowed to stand and passed through a 0.45 μm filter membrane. The adsorption amount was determined and calculated using ICP-MS. Three parallel samples were set for each sample.

[0062] The experimental results were fitted using the Langmuir and Freundlich models, where the Langmuir adsorption isotherm model is shown in formula (3):

[0063] Where: q e is the adsorption amount when reaching equilibrium (mg / g); q m is the adsorption capacity at saturation (mg / g); C e Equilibrium concentration (mg / L); K L is the Langmuir adsorption constant (L / mg).

[0064] The Freundlich adsorption isotherm model is shown in formula (4):

[0065] Where: q e is the equilibrium adsorption capacity (mg / g); K F is the Freundlich adsorption constant (L / mg); C e is the equilibrium concentration (mg / L); n is the Freundlich adsorption characteristic coefficient.

[0066] The adsorption effect of W7FB on arsenic at different times is as follows Figure 7As shown in the figure, the removal rate of arsenic by W7FB showed the characteristics of "rapid adsorption-dynamic equilibrium" in two stages over time: rapid adsorption period and equilibrium stable period. Rapid adsorption period (0-2 hours): the arsenic removal rate increased rapidly from 33.6% to 63.8% (an increase of 90%), indicating that the abundant iron oxide active sites and pore structure on the surface of the material dominated the physical adsorption and chemical complexation of arsenic in the early stage; the removal rate reached 51.7% within 0.5 hours, highlighting its efficient adsorption kinetic characteristics. Equilibrium stable period (2-12 hours): the removal rate fluctuated between 63.8% and 66.4%, reaching a peak of 66.2% in 4 hours, and then fluctuated slightly (such as dropping to 65.8% in 8 hours and recovering to 66% in 12 hours), reflecting the dynamic equilibrium of adsorption-desorption; the metabolic activities of strain W7 (such as arsenic form transformation) may supplement the adsorption sites at this stage to maintain the stable removal rate. W7FB can achieve an arsenic removal rate of over 60% within 2 hours and is close to adsorption saturation (66.2%) in 4 hours. Its rapid response and sustained stability are due to the "adsorption-biotransformation" dual mechanism of bacteria-carbon synergy, and is suitable for emergency remediation scenarios that require rapid reduction of arsenic pollution.

[0067] The fitting results of the arsenic adsorption process of W7FB by pseudo-first-order and pseudo-second-order kinetic models are shown in Figure 8 And as shown in Table 4. Among them, Figure 8 A in the figure is a pseudo-first-order kinetic model. Figure 8 B is the pseudo-second-order kinetic model. Figure 8 The ordinate of A is the common logarithm of the adsorption amount difference, and the corresponding mathematical formula is lg (qe-qt), which represents the common logarithm of the difference between the adsorption amount at adsorption equilibrium (qe) and the adsorption amount at adsorption time t (qt). It reflects the gap between the adsorption amount of the adsorbent on the adsorbate and the equilibrium adsorption amount as time goes by during the adsorption process. Figure 8 The vertical axis of B is the ratio of time to adsorption amount, and the corresponding mathematical formula is t / qt, which means the ratio of time t to adsorption amount qt at time t. It reflects the time required for unit adsorption amount during the adsorption process.

[0068] Table 4 Fitting results of pseudo-first-order and pseudo-second-order kinetic models for the arsenic adsorption process of W7FB

[0069] k in Table 4 1 is the pseudo-first-order kinetic rate constant, k 2 is the pseudo-second-order kinetic rate constant, R 2 is the determination coefficient.

[0070] pass Figure 8The fitting data of the pseudo-first-order and pseudo-second-order kinetic models for the arsenic adsorption process of W7FB in Table 4 show that the adsorption behavior is more consistent with the pseudo-second-order kinetic model (R²=0.999), indicating that the adsorption process is dominated by chemical adsorption mechanisms (such as surface complexation, ion exchange or chemical bond formation) rather than simple physical diffusion. Specifically, the pseudo-first-order kinetics (R²=0.605) has a low fitting degree, indicating that the adsorption rate is not only driven by the arsenic concentration gradient in the solution; the high correlation of the pseudo-second-order kinetics (R²≈1) indicates that the adsorption is rate-limited by the chemical reaction at the active site, and the rate constant k 2 =0.013 g / (mg·h) further verified the typical characteristics of chemical adsorption; the adsorption mechanism was inferred: the iron oxides on the surface of iron-modified biochar were bound to arsenate through coordination bonds, and the metabolites of strain W7 may synergistically enhance the stability of chemical adsorption sites. The arsenic adsorption process of W7FB is mainly chemical adsorption, and its high efficiency is due to the strengthening of active sites under the synergistic effect of bacteria and carbon. This feature has significant advantages in the remediation of high arsenic contaminated water bodies.

[0071] The fitting results of the isothermal adsorption model are shown in Fig. 9 And as shown in Table 5.

[0072] Table 5 Fitting results of isothermal adsorption model

[0073] Q in Table 5 max The maximum adsorption capacity is the maximum adsorption amount when the adsorbent surface is completely covered with a monomolecular layer (in mg / g), which reflects the theoretical limit adsorption capacity of the adsorbent and is related to the number of active sites of the adsorbent. max =118.584 mg / g indicates the maximum capacity of the adsorbent under ideal monolayer adsorption. K L is the Langmuir adsorption constant, which reflects the binding strength between the adsorbent and the adsorbate (in L / mg); the larger the value, the tighter the binding between the adsorbate and the adsorbent, that is, the easier the adsorption occurs; the smaller the value, the weaker the binding between the adsorbate and the adsorbent. 1 / n is the heterogeneity factor, which represents the heterogeneity of the adsorbent surface and the adsorption affinity distribution (dimensionless), where 1 / n<1 means that the adsorption surface is uneven and the adsorption process is easy (preferentially adsorbing high affinity sites); 1 / n>1 means that the adsorption surface is uniform and the difficulty of adsorption increases with the increase of coverage; 1 / n = 1 means degeneration to linear adsorption (similar to Henry's law). K F It represents the Freundlich adsorption constant, which reflects the relative adsorption capacity of the adsorbent (unit: (mg / g)·(L / mg). The larger the value, the stronger the adsorption capacity of the adsorbent for the adsorbate. R² is the determination coefficient, which indicates the goodness of fit of the model to the experimental data. The closer it is to 1, the more reliable the model is.

[0074] Through Fig. 9 The fitting results in Table 5 show that the arsenic adsorption of W7FB is dominated by monolayer chemical adsorption (Langmuir model). At the same time, due to the surface heterogeneity (Freundlich model), it exhibits a wide concentration adaptation range. Its ultra-high adsorption capacity (Q max About 118.6 mg / g) and controllable bonding strength (K L The synergistic properties of the product (about 0.026) make it suitable for arsenic pollution remediation in multiple scenarios, from low-concentration groundwater (μg / L level) to high-concentration industrial wastewater (mg / L level).

[0075] (5) The remediation effect of different dosages on water bodies at different temperatures In order to study the ability of W7-loaded iron-modified biochar materials to adsorb arsenic in aquatic environments at different temperatures and different application amounts, the arsenic-contaminated aquatic environment was simulated, and a solution with an arsenic concentration of 50 mg / L was prepared. 1 g / L, 2 g / L, 3 g / L, and 5 g / L of W7 powder, iron-modified biochar, and W7-loaded iron-modified biochar materials were added, respectively. The solution was cultured at 10°C, 20°C, and 30°C on a constant temperature oscillator at 150 r / min for 24 h, centrifuged at 5000 r / min for 5 min, and the supernatant was filtered through a 0.45 μm filter membrane to determine its As concentration and calculate the adsorption amount. The results are shown in Figure 2. Fig.10 As shown, W7 is strain W7, FB-3 is iron-modified biochar, and W7FB is the composite material of biochar FB-3 loaded with bacteria W7; the letters marked on the figure (such as a, b, c) represent the results of the multiple comparison test, which are used to intuitively display the significant differences between different groups.

[0076] from Fig.10 It can be seen that under the conditions of 10℃, 20℃ and 30℃, the removal rates of arsenic by strain W7 (W7), iron-modified biochar (FB) and their composite materials (W7FB) showed significant temperature dependence, synergistic enhancement and dosage optimization characteristics: Temperature increase enhanced removal efficiency: W7FB still performed excellently at low temperature (10℃) (removal rate of 60.8% at 3 g / L), but as the temperature increased to 20℃ and 30℃, the efficiency further increased to 65.8% and 66.8%, indicating that the activity and adsorption kinetics of the strain were positively regulated by temperature; Single component response differences: W7 powder: at 10℃→30℃, the removal rate increased from 21.4% to 30.8% at 3 g / L, an increase of 44.0%, reflecting the significant promotion of temperature on bacterial metabolism; FB: at 10℃→30℃, the removal rate increased from 54.2% to 60.2% at 3 g / L, an increase of 11.1%, mainly relying on physical adsorption, and the temperature effect was weak.

[0077] Stability of synergistic effect: The synergistic advantage of W7FB is maintained in a wide temperature range: at 10°C, W7FB increased by 12.2% and 184.1% compared with FB / W7 at 3 g / L addition; at 30°C, the increase was 10.9% (vs FB) and 117.0% (vs W7), indicating that bacteria-charcoal synergy is still the dominant mechanism at high temperatures. Synergistic mechanism: Biochar provides a heat-insulating microenvironment for the strain at low temperatures, and at high temperatures, it enhances the exposure of the active sites of the bacteria through the pore structure, forming a dynamic adaptation.

[0078] Dosage optimization and saturation effect: Optimum dosage: 3 g / L is the efficiency inflection point at each temperature (e.g., the removal rate of 3 g / L W7FB is 66.8% at 30°C, and 5 g / L only slightly drops to 66.7%). It is recommended to use 3 g / L as the economic dosage threshold; Dosage-temperature interaction: A higher dosage is required at low temperature (10°C) to compensate for the activity loss (60.8% at 3 g / L); A low dosage (2 g / L) can achieve a removal rate of 57.1% at high temperature (30°C), which is suitable for resource-constrained scenarios. Conclusion: W7FB shows high efficiency in arsenic removal in the range of 10-30°C, and its synergistic effect is not limited by temperature, and 3 g / L is the universal optimal dosage. This material has both low-temperature adaptability and high-temperature activity enhancement characteristics, and is suitable for arsenic pollution control in scenarios with significant seasonal temperature differences or industrial wastewater temperature fluctuations.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An arsenic wastewater treatment agent, characterized in that: It comprises a carrier and a bacterial suspension adsorbed and fixed on the carrier; The carrier is iron-modified biochar; The strain in the bacterial suspension is Bacillus subtilis (Bacillus subtilis) W7.

2. The arsenic wastewater treatment agent according to claim 1, characterized in that: The mass ratio of carbon to iron in the iron-modified biochar is 1: (0.025-1.5); The iron-modified biochar has a pH of 8-9, a conductivity of 1800-1900 μs / cm, an ash content of 25-30 wt%, and a specific surface area of ​​10-12 m 2 / g, with a total pore volume of 0.05-0.07cm 3 / g, the average pore size is 20-22nm, the adsorption pore diameter is 22-24 nm, and the desorption pore diameter is 17-19 nm.

3. The arsenic wastewater treatment agent according to claim 1, characterized in that: The OD600 of the bacterial suspension is 0.9-1.1; the ratio of the carrier to the bacterial suspension is 1 g: (5-30) mL.

4. A method for preparing an arsenic wastewater treatment agent according to any one of claims 1 to 3, characterized in that: The following steps are involved: Under sterile conditions, the iron-modified biochar is mixed with the bacterial suspension and then freeze-dried to obtain the biochar.

5. The method for preparing an arsenic wastewater treatment agent according to claim 4, characterized in that: The method for preparing the iron-modified biochar comprises the following steps: (1) The straw powder is heated to 350-450°C under anaerobic conditions, kept warm for 1-3 hours, cooled to room temperature, and sieved to obtain biochar; (2) Add water to the mixture of biochar and iron source for reaction, dry it, heat it to 350-450°C under anaerobic conditions, keep it warm for 0.5-1h, cool it to room temperature, and seal it to obtain iron-modified biochar.

6. The method for preparing an arsenic wastewater treatment agent according to claim 5, characterized in that: In step (1), the particle size of the straw powder is less than 1 mm, and the particle size of the biochar is 0.053-1 mm; In step (2), the iron source is one of ferric nitrate nonahydrate, ferrous chloride, ferric chloride and ferric sulfate; The mixing mass ratio of the biochar to the iron in the iron source is 1: (0.025-1.5); The solid-to-liquid ratio of the mixture to water is 1 g: (25-35) mL; The reaction is carried out at a constant temperature of 25-30°C and a shaking reaction at 150-200 r / min for 10-15 hours; The drying temperature is 50-60°C.

7. The method for preparing an arsenic wastewater treatment agent according to claim 4, characterized in that: The preparation method of bacterial suspension comprises the following steps: Bacillus subtilis ( Bacillus subtilis ) W7 is inoculated into a sterilized LB liquid medium and cultured in the dark to obtain a seed solution, the seed solution is mixed with the sterilized medium, and the culture is continued in the dark to obtain a bacterial suspension; The sterilization temperature is 121°C for 0.5-1h; the light-proof culture is a constant temperature culture of 25-30°C with shaking at 150-200r / min for 20-25h; The continued dark-proof culture is carried out at a constant temperature of 25-30° C. and a shaking culture at 150-200 r / min for 1-2 days; The volume ratio of the seed solution to the sterilized culture medium is 1:(20-30); The OD600 in the seed solution is 0.6-1; The OD600 of the bacterial suspension is 0.9-1.

1.

8. The method for preparing an arsenic wastewater treatment agent according to claim 4, characterized in that: The ratio of the iron-modified biochar to the bacterial suspension is 1 g: (5-30) mL; The mixing is carried out at a constant temperature of 30-40°C and at a shaking speed of 150-200 r / min for 1-12 hours; The freeze-drying temperature is first freezing at -75~ -85°C for 0.5-2h, and then freezing at -45~ -55°C under vacuum for 20-30h.

9. Use of the arsenic wastewater treatment agent according to any one of claims 1 to 3 in arsenic-contaminated water.

10. A method for treating arsenic wastewater, characterized in that: Applying the arsenic wastewater treatment agent according to any one of claims 1 to 3 to an arsenic-contaminated water body; The arsenic content in the water body is 0-100 mg / L, and the temperature of the water body is 10-30°C; The application amount of the arsenic wastewater treatment agent is 1-5 g / L, and the application time is 20-30 hours.

Citation Information

Patent Citations

  • Functional strains that reduce heavy metal content and improve vegetable quality and their applications

    CN111718870B

  • Magnetic biochar suitable for loading bacillus as well as preparation method and application of magnetic biochar

    CN111206027A

  • Functional strain capable of reducing vegetable heavy metal content and improving vegetable quality, and application

    CN111718870A

  • Iron and manganese oxide-biomass charcoal-microorganism combined adsorption material for cadmium and arsenic combined pollution remediation and preparation method thereof

    CN113426419A

  • Charcoal-loaded biological iron and manganese oxide material and preparation method and application thereof

    CN113604226A

Cited By

  • Preparation process of ferric salt-chitosan composite modified microbial high-adaptability biochar

    CN120866293A

  • Preparation process of iron salt-chitosan composite modified microbial high-adaptability biochar

    CN120866293B